G613 Children's nurses: Influencing policy and practice. (27th April 2016) - Hollis, R; Corkin, D; Crawford, D; Rigby, L
Abstract : Theme 'Working together across boundaries' (generating best practice for C&YP). The Royal College of Nursing (RCN) provides a focus for the 'field of practice' which brings together the work of five professional Forums which encompass the breadth of child health care. These UK nurse practitioners, managers, educationalists and researchers work collaboratively with the college's Professional Lead and in partnership with each other to influence nursing policy and practice throughout the four countries and beyond. The Forums promote children's nursing as a unique part of the nursing paradigm, whilst generating best practice for C&YP, which is fundamental within our profession standards. 1 Methods: Collaborative work of these CYP Forums (Specialist Care; Acute Care; Continuing and Community Care; Professional Issues; Staying Healthy): is to promote and deliver high quality evidence- based nursing care of CYP and their families. are a focus for RCN members committed to nursing CYP, providing them with networks and opportunities for support, advice and professional development. are a voice for children and young people's nursing influence and lobby external organisations to ensure the voice of CYP and those nurses working with them, is heard. Results: Effective communication is extremely important and key to strategy process when raising the profile of children's nursing. Each CYP Forum has a website www.rcn.org.uk identifying committee members, new links to Facebook and Blogs, a wide range of resources and policy/guidance documents 2, 3 which are regularly updated. Conference events such as the RCPCH/RCN Conference and RCN Congress which has the biggest gathering of the 'nursing family' are highlighted and scheduled throughout the year. Members highly value the work of the CYP Forums and exposure to the various levels of professional activity. 4 Conclusions: These Forums support professional activity focussed on the care of children and young people and provide members with access to on-line resources and opportunities for networking; sharing information and best practice. They help children's nurses and nursing students keep up-to-date with their personal and professional development, as well as influencing healthcare improvements for CYP. References: Nursing & Midwifery Council (NMC, 2015) The Code: Professional standards of practice and behaviour for nurses and midwives. London: NMC Royal College of Nursing (RCN, 2013) Supporting parents and health care professionals when breaking bad news: RCN best practice guidance. London: RCN Royal College of Nursing (RCN, 2014) Specialist and advanced children's and young people's nursing practice in contemporary health care: guidance for nurses and commissioners. London: RCN Royal College of Paediatrics and Child Health (RCPCH, 2015) Facing the Future: together for child health. London: RCPCH